2010
DOI: 10.1351/pac-con-10-02-39
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catalysis: A solution for environmental problems

Abstract: The combination of a nonthermal, atmospheric plasma with a catalyst is investigated as a means of destroying pollutants in waste gas streams. Using the examples of dichloromethane (DCM) and toluene in air streams, it is shown that the destruction of the pollutant can be increased whilst lowering the operating temperature, giving increasing energy efficiency. Unwanted by-products can also be reduced selectively by appropriate choice of catalyst and of the plasma-catalyst configuration. By studying the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
99
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 15 publications
(15 reference statements)
0
99
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] It has also been widely documented that the exposure of organic molecules dissolved in water to various forms of plasma discharges leads to their oxidation. [2][3][4][9][10][11] These oxidation phenomena find applications ranging from environmental remediation [9,[11][12][13][14] to water cleaning [10,15] and sterilization. [1,10] Oxidation also plays an important role in many industrial processes such as the conversion of methanol to formaldehyde.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It has also been widely documented that the exposure of organic molecules dissolved in water to various forms of plasma discharges leads to their oxidation. [2][3][4][9][10][11] These oxidation phenomena find applications ranging from environmental remediation [9,[11][12][13][14] to water cleaning [10,15] and sterilization. [1,10] Oxidation also plays an important role in many industrial processes such as the conversion of methanol to formaldehyde.…”
mentioning
confidence: 99%
“…Plasma catalysis is gaining increasing interest for various environmental applications, such as gaseous pollutant removal, the splitting of CO 2 , hydrogen generation and O 3 production [1][2][3][4][5][6][7][8][9]. Plasma catalysis can be regarded as the combination of a plasma with a catalyst, and often results in improved performance, in terms of selectivity and energy efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Packed bed dielectric barrier discharge (DBD) is being increasingly used as a chemical reactor for remediation of environmental pollutants (e.g., NOx, SOx, and VOCs), and conversion of greenhouse gases to useful chemicals. [1][2][3] The non-equilibrium nature of DBD provides major advantage, by allowing operation at atmospheric pressure and ambient conditions. This helps to overcome the thermodynamic barriers in chemical reactions and provides high reactivity at room temperatures.…”
mentioning
confidence: 99%
“…2,6 Additional features such as easy operation, moderate capital cost, and simple scalability have led to extensive research on packed bed DBDs. 7 Several studies which have used packing material in conjunction with plasma in a DBD have found enhanced performance in comparison to a plasma alone system; 2,3,6,[8][9][10][11][12] however, many studies have also reported a negative impact on the performance. 9,[13][14][15] This unfavorable response has been shown to be related to packing configuration and the void fraction of the discharge in the packed bed DBD.…”
mentioning
confidence: 99%